2016
DOI: 10.3389/fmicb.2016.00984
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of 14 Erythrobacter Genomes Provides Insights into the Genomic Divergence and Scattered Distribution of Phototrophs

Abstract: Aerobic anoxygenic phototrophic bacteria (AAPB) are bacteriochlorophyll a (Bchl a)-containing microbial functional population. Erythrobacter is the first genus that was identified to contain AAPB species. Here, we compared 14 Erythrobacter genomes: seven phototrophic strains and seven non- phototrophic strains. Interestingly, AAPB strains are scattered in this genus based on their phylogenetic relationships. All 14 strains could be clustered into three groups based on phylo-genomic analysis, average genomic nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 61 publications
1
24
0
Order By: Relevance
“…Intriguingly, the PGC of Erythrobacter sp. AP23 is closely related to that of Citromicrobium (Zheng et al , 2016). Moreover, the Gemmatimonadetes strain AP64 is a novel organism that contains bacteriochlorophyll a (BChl a), and has been suggested to have acquired its PGC from photoheterotrophic bacteria of the Proteobacteria via an ancient horizontal gene transfer (HGT) event (Zeng et al , 2014).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Intriguingly, the PGC of Erythrobacter sp. AP23 is closely related to that of Citromicrobium (Zheng et al , 2016). Moreover, the Gemmatimonadetes strain AP64 is a novel organism that contains bacteriochlorophyll a (BChl a), and has been suggested to have acquired its PGC from photoheterotrophic bacteria of the Proteobacteria via an ancient horizontal gene transfer (HGT) event (Zeng et al , 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The large PGC superoperon is approximately 35–50 kb in length and contains approximately 40 genes required for the biosynthesis of bacteriochlorophyll, carotenoids, photosynthetic reaction complexes, and light harvesting complexes, in addition to other regulatory functions (Beatty, 1995; Liotenberg et al , 2008; Swingley et al , 2009; Zheng et al , 2011). PGC gene sequences are highly conserved and some essential genes within PGCs (e.g., pufL, pufM, and bchY) in whole PGCs are typically used as molecular markers in phylogenetic analyses to classify phototrophic Proteobacteria and study their ecological diversity and evolutionary relationships (Beja et al , 1992; Yutin et al , 2007; Zeng et al , 2014; Zheng et al , 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Erythrobacter are aerobic anoxygenic phototrophs that conduct photoheterotrophy, have a low BChl a content, and require a source of organic carbon [24,56]. Our endolithic sequences were most similar to those in Group I Erythrobacter genomes [57]. Under our hypothesis, these organisms could still be euendoliths, even though their populations remained low throughout the experiment.…”
Section: Discussionmentioning
confidence: 55%
“…Comparative genomic studies have revealed that the coding potential of different species are highly variable, indicating their divergent evolution (Aylward et al. 2013; Zheng et al. 2016).…”
Section: Introductionmentioning
confidence: 99%